2022
DOI: 10.1186/s12987-022-00348-6
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide modulates intracranial pressure directly by its action on the cerebrospinal fluid secretion apparatus

Abstract: Background Elevated intracranial pressure (ICP) is observed in many neurological pathologies, e.g. hydrocephalus and stroke. This condition is routinely relieved with neurosurgical approaches, since effective and targeted pharmacological tools are still lacking. The carbonic anhydrase inhibitor, acetazolamide (AZE), may be employed to treat elevated ICP. However, its effectiveness is questioned, its location of action unresolved, and its tolerability low. Here, we determined the efficacy and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 79 publications
5
29
0
Order By: Relevance
“…Topiramate reduced ICP to a similar degree as our previous study, where it reduced ICP when administered subcutaneously and in the food of sedated rats (Scotton et al, 2019). Our acetazolamide data are in contrast to some studies and corroborate others, where acetazolamide has been found to either reduce ICP or have no ICP modulatory effect (Barbuskaite et al, 2022;Scotton et al, 2019;Williamson et al, 2019). These previous studies differ from ours through differing administration routes, use of sedation and anaesthesia and the use of inappropriate vehicles: all of which can independently alter ICP (Eftekhari et al, 2020;Uldall et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Topiramate reduced ICP to a similar degree as our previous study, where it reduced ICP when administered subcutaneously and in the food of sedated rats (Scotton et al, 2019). Our acetazolamide data are in contrast to some studies and corroborate others, where acetazolamide has been found to either reduce ICP or have no ICP modulatory effect (Barbuskaite et al, 2022;Scotton et al, 2019;Williamson et al, 2019). These previous studies differ from ours through differing administration routes, use of sedation and anaesthesia and the use of inappropriate vehicles: all of which can independently alter ICP (Eftekhari et al, 2020;Uldall et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…With chronic administration of these drugs in female rats, there was minimal tachyphylaxis. The degree of ICP reduction we observed with chronic acetazolamide is mirrored by that in male rats (Barbuskaite et al, 2022). The equivalent effect of these drugs on ICP mirrors an open label trial where they conferred equivalent retinal outcomes in IIH patients (Çelebisoy et al, 2007).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations